If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -21 = -42 Reorder the terms: -21 + 3x = -42 Solving -21 + 3x = -42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 3x = -42 + 21 Combine like terms: -21 + 21 = 0 0 + 3x = -42 + 21 3x = -42 + 21 Combine like terms: -42 + 21 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| 14-5b=-2(1+7b)-2 | | 4x^2+15x-1=18 | | 4(h-12)=44 | | 8p+2=-54 | | -7(n-3)+2n=-4n+26 | | -7m-12=-40 | | -2(x+8)+5=-23+x | | 7m-20=15 | | 7x+35=180 | | 72+6x=11(14x+20) | | 7m-24=-24 | | 72+6x=11(14x+50) | | -6x-19=-1 | | 8/9-4/5 | | 2/4/-1/2 | | -6(8n+14)-16n=-18n+54 | | -4x-22=6 | | -7m+11=53 | | 5X-19=-21 | | 12=x-(-2) | | -12=-6+3y | | 5/7=3/x | | -10k=20(1-10k)-20 | | -13m-16=36 | | x^7+9x^7= | | 2(16-7p)=-23-9p | | -6p-6=-36 | | 8=vf-3 | | 25=5(7x)-3 | | 15(y+3)=6(y-5) | | X^2-3x-40=o | | 10(v+2)-4v=3(2v+3)-15 |